JASPAR 2018: update of the open-access database of transcription factor binding profiles and its web framework. Issue Volume 46:Issue D1(2018) (13th November 2017) - Khan, Aziz; Fornes, Oriol; Stigliani, Arnaud; Gheorghe, Marius; Castro-Mondragon, Jaime A; van der Lee, Robin; Bessy, Adrien; Chèneby, Jeanne; Kulkarni, Shubhada R; Tan, Ge; Baranasic, Damir; Arenillas, David J; et al.
Abstract: JASPAR (http://jaspar.genereg.net ) is an open-access database of curated, non-redundant transcription factor (TF)-binding profiles stored as position frequency matrices (PFMs) and TF flexible models (TFFMs) for TFs across multiple species in six taxonomic groups. In the 2018 release of JASPAR, the CORE collection has been expanded with 322 new PFMs (60 for vertebrates and 262 for plants) and 33 PFMs were updated (24 for vertebrates, 8 for plants and 1 for insects). These new profiles represent a 30% expansion compared to the 2016 release. In addition, we have introduced 316 TFFMs (95 for vertebrates, 218 for plants and 3 for insects). This release incorporates clusters of similar PFMs in each taxon and each TF class per taxon. The JASPAR 2018 CORE vertebrate collection of PFMs was used to predict TF-binding sites in the human genome. The predictions are made available to the scientific community through a UCSC Genome Browser track data hub. Finally, this update comes with a new web framework with an interactive and responsive user-interface, along with new features. All the underlying data can be retrieved programmatically using a RESTful API and through the JASPAR 2018 R/Bioconductor package.